2022
DOI: 10.1186/s12889-022-12674-3
|View full text |Cite
|
Sign up to set email alerts
|

Employing the theory of planned behaviour to design an e-cigarette education resource for use in secondary schools

Abstract: Background An extended version of the theory of planned behaviour (TPB) was used to inform the design of a framework for an educational resource around e-cigarette use in young people. Methods A sequential exploratory design was employed. In Phase 1, elicited behavioural, normative and control beliefs, via 7 focus groups with 51 participants, aged 11–16 years, identified salient beliefs around e-cigarette use. These were used to construct a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…The TPB has been used extensively to identify factors that influence intentions and explain the underlying cognitive processes towards smoking and to look at quitting behaviour [ [16] , [17] , [18] ]. More recently, the TPB has been used to identify factors that influence e-cigarette use in adolescents and young adults [ [19] , [20] , [21] , [22] ]. Using a shorter version of the theory, Trumbo and Kim found that factors predicting students intention to use an e-cigarette were positive responses to adverts and the belief that they were less addictive [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TPB has been used extensively to identify factors that influence intentions and explain the underlying cognitive processes towards smoking and to look at quitting behaviour [ [16] , [17] , [18] ]. More recently, the TPB has been used to identify factors that influence e-cigarette use in adolescents and young adults [ [19] , [20] , [21] , [22] ]. Using a shorter version of the theory, Trumbo and Kim found that factors predicting students intention to use an e-cigarette were positive responses to adverts and the belief that they were less addictive [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…School-based programs incorporating e-cigarette education into the school curriculum are effective interventions for preventing adolescent e-cigarette use. These programs typically provide students with information on the risks and harms associated with e-cigarette use and strategies for avoiding e-cigarette use [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…The educational component of these programs can include information on the various chemicals found in e-cigarettes, including nicotine, which is highly addictive and can harm adolescent brain development. The programs may also provide information on the potential long-term health consequences of e-cigarette use, such as lung damage, heart disease, and cancer [ 31 , 32 ]. In addition to providing education, school-based programs may teach students specific strategies for avoiding e-cigarette use.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the nine intervention functions were able to map onto the COM-B and the TDF, these included education, training, persuasion, modelling, environmental restructuring and enablement. When considering intervention functions and how appropriate they would be to implement within an intervention, the affordability, practicality, effectiveness, acceptability, safety and equity criteria (87) was applied to each of the six intervention functions in turn, to enhance the appropriateness and suitability of the intervention components (90) .…”
Section: Stage Two: Identifying Intervention Optionsmentioning
confidence: 99%